Isolation of new cellulase and xylanase producing strains and application to lignocellulosic biomasses hydrolysis and succinic acid production. (July 2018) - Pennacchio, Anna; Ventorino, Valeria; Cimini, Donatella; Pepe, Olimpia; Schiraldi, Chiara; Inverso, Michela; Faraco, Vincenza
Highlights: Six Streptomyces with lignocellulose conversion activities were identified. Cellulases and xylanases of two strains were tested in lignocellulose hydrolysis. These enzymes led to better saccharification yield than commercial enzymes. Fermentability of the enzymatic hydrolysates for succinate production was proven. Abstract: The enzymatic extracellular mixtures of two new microorganisms – Streptomyces flavogriseus AE64X and AE63X – isolated from Eucalyptus camaldulensis and Populus nigra and producing cellulase and xylanase, were characterized and applied to hydrolysis of pretreated Arundo donax, Populus nigra and Panicum virgatum (10% w/v) replacing the commercial enzymes Accelerase 1500 and Accelerase XY (5.4 and 145 U/g of pretreated biomass, respectively). It is worth of noting that the newly developed extracellular enzymatic mixtures, without any purification step and at the same dosage, presented saccharification yields that are higher (86% for S. flavogriseus AE64X) than those of commercial enzymes (81%). Moreover, these enzymatic mixes allowed us to hydrolyse both cellulose and xylan within the different lignocellulose biomasses substituting both the cellulase and xylanase of commercial source. The produced sugars were also fermentable by Basfia succiniciproducens BPP7 into succinic acid with high yield.